Geophysical investigations of WWII air-raid shelters in the UK. Issue 3 (2nd September 2018) - Ainsworth, J. T.; Pringle, J. K.; Doyle, P.; Stringfellow, M.; Roberts, D.; Stimpson, I. G.; Wisniewski, K. D.; Goodwin, J.
ABSTRACT: Just before WWII, the British government prepared for an aerial onslaught that was predicted to raze cities and cause mass casualties. By 1938, the Air Raid Precautions Act officially stated that population protection would be through dispersal, meaning evacuation and small-scale protection, local authority responsibility often devolving to householders. Archaeological records of remaining air-raid shelters are relatively rare and under threat. This paper reports on geophysical surveys on three sites in Stoke-on-Trent and London. Results found three intact Stanton shelters in Stoke-on-Trent, located by GPR, electrical resistivity, magnetometry, gravity and electromagnetic methods. In London, partially demolished shelters and an intact, mass public shelter were both detected by EM and GPR methods, with subsequent intrusive investigations confirming results. Study outcomes show hitherto-neglected wartime shelters are in varied condition, with geophysical surveys able to detect, characterise and assess them, helping bring WWII British history into the wider scientific community and public domain.